2001
DOI: 10.1101/gad.943001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lung tumor initiation and progression using conditional expression of oncogenic K-ras

Abstract: Adenocarcinoma of the lung is the most common form of lung cancer, but the cell of origin and the stages of progression of this tumor type are not well understood. We have developed a new model of lung adenocarcinoma in mice harboring a conditionally activatable allele of oncogenic K-ras. Here we show that the use of a recombinant adenovirus expressing Cre recombinase (AdenoCre) to induce K-ras G12D expression in the lungs of mice allows control of the timing and multiplicity of tumor initiation. Through the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,849
4
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,747 publications
(1,958 citation statements)
references
References 19 publications
(22 reference statements)
63
1,849
4
9
Order By: Relevance
“…Lungs from Cre adenovirus‐instilled Kras G12D mice showed hyperproliferation leading to different grades of lung lesions previously reported in mouse lung tumor models (Jackson et al ., 2001; DuPage et al ., 2009) such as bronchioloalveolar hyperplasia, adenoma, and adenocarcinoma (Fig. 1C, Methods S1).…”
Section: Resultsmentioning
confidence: 99%
“…Lungs from Cre adenovirus‐instilled Kras G12D mice showed hyperproliferation leading to different grades of lung lesions previously reported in mouse lung tumor models (Jackson et al ., 2001; DuPage et al ., 2009) such as bronchioloalveolar hyperplasia, adenoma, and adenocarcinoma (Fig. 1C, Methods S1).…”
Section: Resultsmentioning
confidence: 99%
“…We generated a cohort of conditional mutant mice by crossing Lox-Stop-Lox (LSL)-K-ras G12D mice (Jackson et al, 2001) to CC10-Cre mice in which Cre recombinase expression is under control of the Clara cell secretory protein promoter. As with other transgenes driven by CC10 (Perl et al, 2002), Cre expression was limited to the lung bronchiolar epithelium as demonstrated by analysis of the CC10-Cre strain crossed with the ROSA-Stop-LacZ reporter strain (data not shown), which demonstrated the complete absence of LacZ staining beyond the bronchoalveolar duct junction.…”
Section: Cc10-cre/lsl-k-ras G12d Conditional Mutant Mice Develop Lungmentioning
confidence: 99%
“…Of these, only Kras2 is a known target of mutation in lung tumors 3,4 , and mice expressing oncogenic Kras2 have a high incidence of early onset lung cancer 7,8 . Lung tumors from F1-hybrid mice showed a strong bias for Kras2 mutation involving the allele inherited from the more susceptible parent 9 , rendering Kras2 a candidate for Pas1.…”
Section: Introductionmentioning
confidence: 99%